Pentoxifylline May Restore Kanamycin-Induced Renal Damage in Rats - Corum, Orhan; Ozdemir, Ozgur; Hitit, Mustafa; Corum, Duygu Durna; Coskun, Devran; Er, Ayse (Acta Scientiae Veterinariae, 2018)
Background: Kidney damage can be caused by many factors, such as using certain drugs in high doses or over the long term. The use of one such group of drugs, aminoglycosides, which act as Gram-negative antibacterial therapeutic agents, can lead to nephrotoxicity. It has been hypothesized that aminoglycoside-induced nephrotoxicity might be prevented by using pentoxifylline, which has antioxidant and anti-inflammatory effects and improves microcirculation. The objective of this present research was to determine the protective effects of pentoxifylline on kanamycin-induced kidney damage. Materials, Methods & Results: Thirty-two male Wistar rats were divided into four groups as follows: control, pentoxifylline, kanamycin, and kanamycin + pentoxifylline. The control group received intraperitoneal (IP) injections of 0.5 mL normal saline solution once a day (d) (SID) for 20 d; the pentoxifylline group received IP injections of 50 mg/kg pentoxifylline twice a day (BID) for 20 d, the kanamycin group received subcutaneous (SC) injections of 500 mg/kg kanamycin SID for 20 d, and the kanamycin + pentoxifylline group received both SC injections of 500 mg/kg kanamycin SID and IP injections of 50 mg/kg pentoxifylline BID for 20 d. At the end of 20 d, blood samples were taken from the heart by cardiac puncture under general anesthesia. After euthanizing the rats by cervical dislocation under anesthesia, the kidneys were immediately removed, relative kidney weights were calculated, and routine pathologic evaluations were conducted. Hemogram parameters were measured using a blood cell count apparatus and serum biochemical parameters were measured using an autoanalyzer. Kanamycin also caused (P < 0.05) tubular degeneration and tubular dilatation. Although pentoxifylline significantly reduced the level of kanamycin-induced tubular degeneration (P < 0.05), it did not significantly reduce tubular dilatation. Increases in relative kidney weights (P < 0.05) and in interstitial mononuclear cell (MNC) infiltrates were observed in the kanamycin and kanamycin + pentoxifylline groups compared to those in the control and pentoxifylline groups. Statistically significant changes were determined in the levels of some hemogram and biochemical parameters within reference ranges (P < 0.05). Discussion: In this study, both tubular degeneration and dilatation were observed in the kanamycin group. Pentoxifylline inhibited (P < 0.05) kanamycin-induced tubular degeneration and appeared to also reduce tubular dilatation, although this reduction was not significant. Tubular necrosis, epithelial edema of proximal tubules, tubular fibrosis, and perivascular inflammation might also be observed in aminoglycoside-induced nephrotoxicity. In current research, pentoxifylline prevented tubular damage induced by kanamycin, but did not inhibit infiltration by MNCs. Pentoxifylline also ameliorated amikacin- or gentamycin-induced histopathologic changes, especially those associated with tubular structures. The protective effects of pentoxifylline on kanamycin-induced tubular nephrotoxicity in this research might be a result of its stimulating the production of prostaglandin, a vasodilator, and of its improving microcirculation. Although the anti-inflammatory effects of pentoxifylline have been reported, these did not inhibit kanamycin-induced infiltration by interstitial MNCs in the present study. These results could indicate that the anti-inflammatory effects of pentoxifylline are not obvious and/or are dose dependent. Statistically significantly changes were determined in the levels of some hemogram and biochemical parameters in reference ranges. However, these changes were within the reference ranges for rats. These results suggested that kanamycin-induced tubular degeneration and dilatation might be prevented by administering pentoxifylline.